Sistem Informasi Pelayanan Surat Keterangan Desa Jalatrang Berbasis Web - Fianita Rusadi; Yudhistira Arie Wijaya (Manajemen Kreatif Jurnal, 2023)
This study aims to determine the information system service certificate for Jalatrang Village, Ciamis Regency using data collection techniques through field research, namely observation and in-depth interviews with 8 informants who were selectedqualitatively descriptively. The results show that the service information system for village certificates in ciamis district provides positive things to the village. This research was contuted by a library study, namely the collection of data and information through books and other reading sources that are relevant to the problem to be studied. Field research is data obtained by observation. The purpose of this final project is a web-Based Village Certificate Service Information System in Jalatrang Village” aims to design a database that accommodates all information about Jalatrang Village so that this information can be provided and presented more effective in terms of time and energy utilization.